THE SPECIFIC FEATURES OF ECLOGITIC PARAGENESIS OF DIAMONDS FROM MIR AND UDACHNAYA KIMBERLITE PIPES (YAKUTIA) - Sobolev N.V.; Taylor L.A.; Zuev V.M.; Bezborodov S.M.; Snyder G.A.; Sobolev V.N.; Yefimova E.S. (My University, 1998)
The paper summarizes both published and unpublished compositional data of garnets and pyroxenes from eclogitic type (E-type) paragenesis diamonds from Mir and Udachnaya kimberlite pipes (Yakutia). The database includes about 50 xenoliths of diamondiferous eclogites from the Mir pipe, more than 150 similar xenoliths from the Udachnaya pipe, and up to 100 E-type diamonds with inclusions from both pipes. Garnets and pyroxenes from seven new samples of diamondiferous eclogites (three from Mir and four from Udachnaya) are analyzed as well as from four E-type diamonds from the Udachnaya pipe. Two of the diamonds contain abundant garnet and pyroxene inclusions (40 - from Ud-4/90 and 17 - from Ud-10/90). Two other diamonds (Ud = 11/90 and Ud = 20/86) contain coesite inclusions in addition to garnet and pyroxene. Most of the inclusions have imposed octahedral morphologies. Garnets from diamondiferous eclogites form a continuous series of compositions, for both Mg# and Ca#, with most calcic garnets present in kyanite-bearing assemblages. Garnets from Mir eclogites are sometimes zoned and have lower Mg# compared with those from Udachnaya, where about 50% eclogite garnets possess Mg# 65 and more. All E-type garnets from Mir diamonds and eclogites plot within the field of garnet compositions related to diamonds worldwide. In contrast, E-type Udachnaya garnets, especially from diamondiferous eclogites, occupy a much wider compositional field, expanding to higher Mg# side (about 30% of all samples), along with wide variations in Ca#, from 10 to 55%. Pyroxenes from diamondiferous eclogites from both locations contain more Na2O and considerably less K2O when compared to diamond inclusion pyroxenes. This is also confirmed by a study of 10 samples of diamondiferous eclogites containing diamonds with inclusions. Complex and variable of garnet and pyroxene compositions are typical of diamonds from both pipes containing multiple inclusions. Based upon garnet and pyroxene compositions it is concluded that Group A diamondiferous E-type assemblages are virtually absent from the Mir pipe and represent about 20% of all samples from Udachnaya. The wide range of garnet-pyroxene compositions in multiple-inclusion diamonds, as well as between diamond inclusions and minerals of the same host eclogite, reflect the complex growth history of eclogitic diamonds and their hosts, and participation of mantle metasomatic fluids in their formation.